Sources of Motivation Generation Y at Work - Kobyłka , Agata (Studia Oeconomica Posnaniensia, 2016)
Human resource management in contemporary organizations takes the form of more or less planned personnel processes. One of the tools used in their implementation measures is motivating employees, which can be treated as an investment in human capital. The aim of the study was to identify the sources of motivation to work for generation Y. The study was conducted in the period 11.11.2012-31.12.2013. It took the form of an anonymous questionnaire. The study involved 463 respondents (86.8% - students, 13.2% - graduates). The concept of motivational mix assumes that the motivation of employees has a decisive influence of two factors: focus on personal development and the benefits that make up the five sources of motivation. Respondents recognized as the most motivating factors salary, work atmosphere, job security and relationships in the team. The threat of punishment and strict control were discouraging.